Performance Broiler Strain Lohman and Strain Cibadak Raised In Postal with System Semi Clouse House - Martahan Sitorus; Wiesje. M. Horhoruw; Lea M. Rehatta (Universitas Pattimura, 2023)
This study aims to determine performance broiler strain Lohman and strain Cibadak kept in postal cages with the system semi clouse house. Materials of this research namely broiler strain Lohman and Cibadak are kept in postal cages with the system semi clouse house, population of 11,000 head/cage as well as commercial feed types HI-PRO BR10 and HI-PRO BR11+. This panel was conducted for 28 days on Mr. Haji Agus Rifai's farm with a postal cage type in Kentrong Village, Cipanas District, Lebak Regency, Banten. The method used in this research is survey and observation (direct observation in the field) to collect data related to performance broiler. The variables observed in this study were feed consumption, body weight gain, feed convertion rasio (FCR) and depletion. The data obtained were analyzed descriptively. The research results show that performance broiler strain Lohman is better than strain Cibadak, With performance broiler strain Lohman namely feed consumption of 515 gr/head, PBB of 324 gr/head, FCR 1.383 and depletion rate of 4.03%, and performance broiler strain Cibadak namely feed consumption of 616 gr/head, PBB of 369 gr/head, FCR 1.488 and depletion rate of 8.46%.